Analisis Pembiayaan Perumahan Syariah pada Perumahan Balad Residence Property - Arfah, Nafis Ali Muhammad (Jurnal Iqtisaduna, 2024)
This study aims to analyze the Islamic housing financing scheme of Balad Residence Property, focusing on the contract, process, marketing strategies, and risk management from an Islamic perspective. The study is motivated by the increasing demand from Indonesia’s Muslim community for interest-free housing financing, as conventional mortgage schemes contain interest elements that conflict with Islamic principles. The Sharia mortgage scheme has emerged as a solution to address this demand. This research employs a descriptive qualitative method, collecting primary data through field observations and interviews with developers, employees, and consumers. The findings reveal that the financing scheme uses an istisna’ contract (a sales contract based on orders), where consumers make payments directly to the developer without involving a third-party bank. Although this scheme aligns with Islamic principles, its risk management remains insufficient, leading to challenges for both developers and consumers. This study provides valuable insights for developers to improve the Islamic housing financing scheme and offers considerations for consumers when making decisions.